2023
DOI: 10.3920/jiff2023.0010
|View full text |Cite
|
Sign up to set email alerts
|

Grasshoppers and locusts as human foods – a comprehensive review

Abstract: Nutritious and sustainable food sources are much needed to compensate for the rising demand for food due to the ever-growing human population. The idea of using insects as potential future foods is getting more attention globally. The consumption of insects or entomophagy offers several advantages other than fulfilling human nutritional and energy requirements. By considering climate change and the reduction in arable land and water, entomophagy and insect farming is regarded to be more environmentally friendl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…A wide range of insect-based products also affect acceptability of insect-based food providing consumers with diversified options to choose from. This is a crucial strategy to increase consumer acceptance of edible insects (Siddiqui et al, 2023). Tan et al (2016b) found that appropriate product design is important to achieve consumer acceptance of insects as food in the Western countries.…”
Section: Exposurementioning
confidence: 99%
“…A wide range of insect-based products also affect acceptability of insect-based food providing consumers with diversified options to choose from. This is a crucial strategy to increase consumer acceptance of edible insects (Siddiqui et al, 2023). Tan et al (2016b) found that appropriate product design is important to achieve consumer acceptance of insects as food in the Western countries.…”
Section: Exposurementioning
confidence: 99%